An investigation of the impact of NFTs on the Modern Art Market - Mwesigwa, Timothy (School of Economics, 2024)
The adoption of Non-Fungible Tokens (NFTs) and blockchain technology by the art industry, creates a digital art market. NFTs also change the way artists earn a living from their creations and enable digital asset ownership which impacts any potential digital art owners. This thesis reviews the available academic literature on the impact of NFTs on three elements of the art industry; it's structure, it's creators and it's consumers. I find that the history of the art market determined its modern structure, which is divided between primary and secondary markets, each market dealing directly and indirectly for art with original artists, respectively. NFTs foster disintermediation in the secondary art market, made of traditional intermediaries like art dealers, by enabling a more efficient copyright management mechanism on the blockchain. Additionally, because NFTs enable unique digital identification of digital art, they create a new market for digital assets which extend the structure of the art market to encompass the digital realm. However, the current legislation concerning digital property is structured in a way which favours licencing models which do not enable full ownership of digital files. The hybrid nature of NFTs transactions, which have elements of both sales and licensing agreements, creates the main challenge policy-makers face to craft regulation applicable to NFT transactions. Common law plays a crucial role in this process by balancing digital contracting and property rights which ultimately affects investment in digital property. NFTs also enable the implementation of novel funding models for artists on the blockchain. These include fractional equity in art and the efficient payment resale royalties, which are previously put forward through the Artist's contract, but only practically achieved using NFTs, smart contracts and tokenisation on the blockchain. This thesis lays the foundation for subsequent studies to explore other substantial segments of the NFT market, especially the collectables and gaming segments